Developmet of Android E-book Forms of Energy to Improve Students’ Critical Thinking and Mathematical Representation Skills (International Journal of Scientific Research and Management (IJSRM), 2024)
Critical thinking and mathematical representation skills play an important role for students, especially in physics. This research’ aims are to study the feasibility and effectiveness of the android e-book forms of energy to improve students’ critical thinking and mathematical representation skills. This research was developed using the ADDIE model. The experimental design was one group pretest posttest. This research found that the E-book were feasible to be applied in physics learning. It content qualify the writing and content requirements for a physics E-book. The android e-book is effective for improving students’ ability in interpretation and explanation, effective enough in analyze, and less effectively in the inference and argument and evaluation aspects. E-book is less effective in the aspect use pictures, graphs, tables, or diagrams to solve problems and effective enough in training students use symbols or mathematical equations in solving problems and explain data or other representations in sentence form. The global N-Gain value shows that the Android e-book forms of energy is effective enough to improve critical thinking and mathematical representation skills.